Coronaphobia and academic procrastination in health sciences students during the first 3-month pandemic lockdown - Yucel, Hulya; Fatma Kanta Yilmaz; Erim, Ahsen (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the correlation between coronaphobia and academic procrastination among university students during the first 3-month coronavirus disease-2019 lockdown. Method: The cross-sectional study was conducted from June to July 2020 at the Hamidiye Faculty of Health Sciences, the University of Health Sciences, Istanbul, Turkey, and comprised Health Sciences students of either gender across 10 departments. The coronavirus disease-2019 Phobia Scale and the Scale of Academic Procrastination Behaviour were used to gather data. The relationship of the scores was examined with respect to gender and academic level. Data was analysed using SPSS 21. Results: Of the 743 subjects enrolled, 681(91.65%) completed the survey; 548(80.5%) females and 133(19.5%) males. The overall mean age was 20.91±1.94 years (range: 18-35 years). The largest group was that of first year students 229(33.6%). There was a significant correlation between coronaphobia and academic procrastination (p=0.001). Total coronaphobia (p=0.023) and psychological subscale scores (p=0.001) of women were significantly higher than men. Negative perceptions regarding instructors were higher in men than women (p=0.038). The academic year was not significantly associated with either coronaphobia (p=0.249) or procrastination (p=0.546). Conclusion: The coronavirus disease-2019 created a phobia and this caused academic procrastination in health sciences students, especially women. Key Words: COVID-19, Pandemic, Phobia, Procrastination, Education.